Five-year risk of heart failure and death following myocardial infarction with cardiogenic shock: a nationwide cohort study. Issue 1 (4th October 2020) - Lauridsen, Marie Dam; Rorth, Rasmus; Butt, Jawad Haider; Kristensen, Soren Lund; Schmidt, Morten; Moller, Jacob Eifer; Hassager, Christian; Torp-Pedersen, Christian; Gislason, Gunnar; Kober, Lars; Fosbol, Emil Loldrup
Abstract: Aims: More patients survive myocardial infarction (MI) with cardiogenic shock (CS), but long-term outcome data are sparse. We aimed to examine rates of heart failure hospitalization and mortality in MI hospital survivors. Methods and results: First-time MI patients with and without CS alive until discharge were identified using Danish nationwide registries between 2005 and 2017. One-, 5-, and 1- to 5-year rates of heart failure hospitalization and mortality were compared using landmark cumulative incidence curves and Cox regression models. We identified 85 865 MI patients of whom 2865 had CS (3%). Cardiogenic shock patients were of similar age as patients without CS (median age years: 68 vs. 67), and more were men (70% vs. 65%). Cardiogenic shock was associated with a higher 5-year rate of heart failure hospitalization compared with patients without CS [40% vs. 20%, adjusted hazard ratio (HR) 2.90 (95% confidence interval (CI) 2.67–3.12)]. The increased rate of heart failure hospitalization was evident after 1 year and in the 1- to 5-year landmark analysis among 1-year survivors. All-cause mortality was higher at 1 year among CS patients compared with patients without CS [18% vs. 8%, adjusted HR 3.23 (95% CI 2.95–3.54)]. However, beyond the first year, the mortality for CS was not markedly different compared with patients without CS [12% vs. 13%, adjusted HR 1.15 (95% CI 1.00–1.33)]. Conclusion: Among MI hospital survivors, CS was associated with a markedly higher rate of heart failure hospitalization and 1-year mortality compared with patients without CS. However, among 1-year survivors, the remaining 5-year mortality was similar for MI patients with and without CS.